Klanceng Honey Beehive (Trigona biroi) Sunscreen Activity - Purwaningsih, Yuliana; Masduqi, Ahmad Fuad; Indriyanti, Erwin (Universitas Jenderal Soedirman, 2025)
ABSTRACT. UV radiation can cause various skin problems, including photoaging and skin cancer. Sunscreen can provide UV radiation protection. Klanceng honey bee nests may contain metabolites that could be employed as sunscreen agents. This research project investigates the sunscreen activity of the extract, n-hexane fraction, ethyl acetate fraction, and aqueous fraction of the Klanceng honey bee hive using SPF, % Te, and Tp values. Honey bee hives are extracted via maceration assisted by ultrasonic waves. As solvents for fractionation, n-hexane, ethyl acetate, and water are used. UV spectrophotometry at a wavelength of 290-375 nm was used to examine the sunscreen activity of the samples in vitro, and the SPF, % Te, and % Tp values were computed. The extract, n-hexane fraction, ethyl acetate fraction, and aqueous fraction had SPF values of 5.832, 4.464, 11.898, and 2.846, with medium, medium, maximum, and minimal protection categories, respectively. The % Te value indicates that the extract, n-hexane, and aqueous fraction do not protect anti-erythema transmission. However, the ethyl acetate fraction does. The % Tp statistic demonstrates that all samples offer sunblock category protection. Based on this, the availability of ethyl acetate fraction is the most effective defense against UV A and UV B rays, indicating that it has the most significant potential as a sunscreen agent. Keywords: Erythema, Pigmentation, Honey bee hive, SPF, Sunscreen